Boosted hydrogen evolution activity from Sr doped ZnO/CNTs nanocomposite as visible light driven photocatalyst. (3rd August 2021) - Ahmad, Irshad; Shukrullah, Shazia; Naz, Muhammad Yasin; Rasheed, Muhammad Athar; Ahmad, Mukhtar; Ahmed, Ejaz; Akhtar, Muhammad Shoaib; Khalid, N.R.; Hussain, Abid; Khalid, Sadia
Abstract: CNTs were decorated onto Sr doped ZnO nanoparticles to construct an efficient photocatalyst via a facile sol-gel method. The as-fabricated Sr doped ZnO/CNTs with recyclability exhibits Sr and CNTs content dependent hydrogen evolution activit under visible light illumination. The Sr doped ZnO/CNTs photocatalyst shows the highest hydrogen evolution rate of 2732.2 μmolh −1 g −1, which is 33.7 and 2.83 times higher than pure ZnO and Sr doped ZnO photocatalysts, respectively. The improved hydrogen evolution activity of Sr doped ZnO/CNTs is primarily assigned to high surface area, Sr doping and construction of heterojunction, which can extend the light absorption, decrease the optical band gap and improve the charge separation. Moreover, the underlying photocatalytic mechanism is proposed on the basis of Mott-Schottky study and explains the interfacial charge transfer process from ZnO to CNTs and Sr. This work open new strategies to synthesize CNTs based nanocomposite for hydrogen evolution. Highlights: Sr doped ZnO and Sr doped ZnO/CNTs successfully synthesized via sol-gel method. PL and EIS confirmed the prolong electron-hole separation over Sr doped ZnO/CNTs. Sr doped ZnO/CNTs possess abundant active sites and least impedance. Sr doped ZnO/CNTs showed much higher hydrogen evolution than pure and Sr doped ZnO. High stability and recyclability over Sr doped ZnO/CNTs was confirmed.